Estimation of De Facto Flexibility Parameter and Basket Weights in Evolving Exchange Rate Regimes - Frankel, Jeffrey; Xie, Daniel (American Economic Review, 2010)
Estimation of De Facto Flexibility Parameter and Basket Weights in Evolving Exchange Rate Regimes by Jeffrey Frankel and Daniel Xie. Published in volume 100, issue 2, pages 568-72 of American Economic Review, May 2010